Keragaman Limnofitoplankton Di Danau Lait Kecamatan Tayan Hilir Kabupaten Sanggau - Ari Hepi Yanti, Destine Pravitaningtyas Putrianti, Tri Rima Setyawati (Jurnal Protobiont, 2015)
The Lait lake is a lake that serves as a source of water, a place for fishing, a transportation route and a recreational spot that will affect the existing limnophytoplankton. This research aims to determine the composition, abundance and diversity of limnophytoplankton, as well as the physical-chemical conditions of the limnophytoplankton habitat in the Lait Lake. The study was conducted from August to December 2014. The sampling location was divided into six stations. The results of the research found 51 genera of limnophytoplankton that were included in five divisions (Chrysophyta, Chlorophyta, Cyanophyta, Euglenophyta and Phyrrophyta) and 6 classes (Bacillariophyceae, Chrysophyceae, Chlorophyceae, Cyanophyceae, Euglenophyceae, and Dinophyceae). The diversity index value (H’) of the limnophytoplankton in the Lake was included in the category of medium (1.2498-2.1353), and the dominance index (D) was low (0.1866-0.4601) and the evenness index (E) was medium (0.3804-0.6161). The physical-chemical condition of the body of water of the Lait Lake was still capable of supporting the life of the existing limnophytoplankton.